Bibliometric Mapping and Narrative Review of Macroergonomics in Modern Industry - Mohammad Fajar Nurwildani; Hari Purnomo; Hartomo Soewardi; Elisa Kusrini (Institut Teknologi Dirgantara Adisutjipto, 2026)
The rapid acceleration of modern industry driven by automation and AI requires a systematic approach to aligning workers, technology, and organizations, a role addressed by macro ergonomics. This study maps the intellectual structure and evolution of macro ergonomics in modern industrial contexts through a hybrid systematic literature review and bibliometric analysis of 233 Scopus-indexed documents. Using R-based bibliometric methods, key trends, collaboration networks, and thematic clusters were identified. The findings show that macro ergonomics has evolved into a critical sociotechnical framework for Industry 4.0/5.0, supporting organizational resilience, safe human–AI integration, and the reduction of systemic risks in automated environments. Three dominant research themes emerge: digital integration, organizational optimization, and human-centered design, alongside notable gaps in global collaboration and SME applications. Overall, this study consolidates the scientific landscape of macro ergonomics and provides guidance for future research and practical implementation of holistic, adaptive, and human-centric work systems.